Development of Oral Communicative Competence Among Students of NonLinguistic Universities in the Context of Digital Transformation (Eurasian Scientific Herald, 2026)
The article examines the development of oral communication skills among students of non-linguistic universities in the context of digitalization and reduced classroom hours. The relevance of the study is determined by the need to improve the quality of foreign language training under conditions of limited instructional time and increasing group sizes. The aim of the research is to identify effective ways to intensify the learning process with a focus on developing oral communicative competence. The study employs methods such as literature analysis, pedagogical observation, and experimental teaching. The authors substantiate the effectiveness of interactive teaching methods, including roleplaying, project-based learning, case studies, and presentations, as well as the use of digital educational resources. Particular attention is given to the organization of independent student work and the creation of a success-oriented learning environment. The findings demonstrate that the integrated application of these approaches enhances student motivation, increases speech activity, and improves the overall quality of learning outcomes.